15 years of the Institute of Ecology and Bioethics at the Cardinal Stefan Wyszyński University in Warsaw - Uchmański, Janusz; Latawiec, Michał; Czartoszewski, Jacek; Ilieva-Makulec, Krassimira (Studia Ecologiae et Bioethicae, 2017)
In 2017, 15 years have passed since the establishment of the Institute of Ecology and Bioethics as part of the Faculty of Christian Philosophy at the Cardinal Stefan Wyszyński University in Warsaw. It is therefore 15 years of leading the field of environmental protection. Humanistic aspects of environmental protection were undertaken before 2002. Therefore, it is worth recalling the history and the main organizers of the Institute of Ecology and Bioethics, showing the evolution of the research problems undertaken and signaling the proposed further research and scientific development.